Composite thermal insulation material and preparation method thereof

By using composite insulation insulation materials, the thermal insulation effect and safety performance of the existing rubber and plastic insulation pipes in the heating pipeline of the swimming pool have achieved better thermal insulation, strength, aging and corrosion resistance.

CN119331319AActive Publication Date: 2025-01-21LANDY GUANGZHOU PLASTIC PROD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411457885.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing rubber and plastic insulation pipes in swimming pool hot water pipes affect the insulation effect and safety performance due to corrosion, especially in alkaline water quality and high chloride ion environments.

Method used

Composite thermal insulation material is used, which is composed of nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, modified fillers, flame retardants, etc., and is vulcanized and foamed through a specific preparation method to form an excellent thermal insulation, Materials for strength, aging resistance and corrosion resistance.

Benefits of technology

The composite thermal insulation material has significantly improved the thermal insulation effect and safety performance of the heating water pipeline during the use of the swimming pool, enhanced corrosion resistance and aging resistance, while ensuring better flame retardability and thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090997370000071
    Figure BDA0005090997370000071
Patent Text Reader

Abstract

The invention relates to the field of thermal insulation materials, in particular to a composite thermal insulation material and a preparation method thereof. Comprising 55-75 parts of nitrile rubber, 20-40 parts of butadiene styrene rubber, 16-32 parts of polyvinyl chloride, 5-10 parts of an ethylene-vinyl acetate copolymer, 13-26 parts of a modified filler, 6-12 parts of a flame retardant, 1-3 parts of a lubricant, 2.1-3.5 parts of a vulcanizing agent, 1.5-3 parts of a foaming agent and 0.6-1.2 parts of an anti-aging agent. The composite thermal insulation material prepared by the invention not only has excellent thermal insulation property, but also has more excellent strength, aging resistance and corrosion resistance than common rubber and plastic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermal insulation materials, and in particular to a composite thermal insulation material and a preparation method thereof. Background Art

[0002] In the construction and maintenance of swimming pools, the insulation of hot water pipes is crucial. This is not only related to the stability and comfort of the swimming pool water temperature, but also affects the energy consumption and environmental protection and energy saving issues. The swimming pool hot water pipe is mainly used to circulate the heated water in the swimming pool to maintain the water temperature. Therefore, while the pipe is subjected to high-temperature water transportation, it must also have the characteristics of corrosion resistance, pressure resistance, and good sealing performance. In recent years, rubber-plastic insulation pipes have been widely used in many fields as an efficient and environmentally friendly insulation material. Rubber-plastic insulation pipes are insulation pipes made of rubber and plastic materials as the main raw materials. They have low thermal conductivity and good fire resistance. They can effectively reduce heat loss, maintain stable water temperature, and improve safety. In addition, the swimming pool environment is usually humid. Rubber-plastic insulation pipes can effectively prevent water penetration and keep the interior dry. The applicable temperature range of rubber-plastic insulation pipes is generally between -50℃ and +110℃. The temperature of the general swimming pool hot water system is usually below 40-80 degrees Celsius. Therefore, from a technical point of view, swimming pool hot water pipes can be wrapped with rubber-plastic insulation pipes. Within this range, the rubber-plastic insulated pipe can maintain its stable physical and chemical properties, provide excellent insulation effect and improve energy utilization efficiency.

[0003] Although rubber-plastic insulation pipes have great advantages and are of high application value in the insulation of hot water pipes in swimming pools, in actual use, due to the complex composition of swimming pool water, which is generally alkaline, and contains a large amount of chloride ions, the rubber-plastic insulation pipes will be greatly affected by long-term corrosion, and their insulation effect and safety performance. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a composite thermal insulation material and a preparation method thereof.

[0005] The purpose of the present invention is achieved by the following technical solutions:

[0006] In a first aspect, the present invention provides a composite thermal insulation material, calculated by weight, comprising:

[0007] 55-75 parts of nitrile rubber, 20-40 parts of styrene-butadiene rubber, 16-32 parts of polyvinyl chloride, 5-10 parts of ethylene-vinyl acetate copolymer, 13-26 parts of modified filler, 6-12 parts of flame retardant, 1-3 parts of lubricant, 2.1-3.5 parts of vulcanizing agent, 1.5-3 parts of foaming agent and 0.6-1.2 parts of antioxidant.

[0008] Preferably, the type of the nitrile rubber is one of NBR2707, NBR2870 and NBR3345.

[0009] Preferably, the type of the styrene-butadiene rubber is one of SBR1500E, SBR1502 and SBR1712.

[0010] Preferably, the parameters of the ethylene-vinyl acetate copolymer (EVA) are: vinyl acetate (VA) content of 18 wt % and melt index of 8 g / 10 min (190° C. / 2.16 kg).

[0011] Preferably, the melt index of the polyvinyl chloride is 13-18 g / 10 min (190°C / 2.16 kg) and the density is 1.36-1.39 g / cm 3 .

[0012] Preferably, the flame retardant is an inorganic silicon-based flame retardant, including any one of aluminum silicate, calcium silicate, and potassium aluminum silicate.

[0013] Preferably, the lubricant is any one of magnesium stearate, zinc stearate and sodium stearate.

[0014] Preferably, the vulcanizing agent is a mixture of sulfur and zinc dimethacrylate in a mass ratio of 3-6:1.

[0015] Preferably, the foaming agent is any one of foaming agent AC, foaming agent H, and foaming agent OBSH.

[0016] Preferably, the antioxidant is any one of antioxidant 264, antioxidant 4010, antioxidant 3100, and antioxidant 4020.

[0017] Preferably, the preparation method of the modified filler comprises:

[0018] S1, γ-aminopropyltriethoxysilane and ethanol solution are mixed, heated and refluxed for 2-4 hours, then allophane powder is added, refluxed for 6-10 hours, filtered, washed and dried to obtain aminosilane-modified allophane;

[0019] S2, dissolving allyl alcohol glycidyl ether in anhydrous ethanol, heating and refluxing for 0.3-0.8h, then adding aminosilane-modified allophane, continuing to reflux and stir for 2-6h, filtering, washing and drying to obtain allyl-modified allophane;

[0020] S3. Add allyl-modified allophane, 2-mercaptobenzimidazole and initiator into tetrahydrofuran, place under ultraviolet lamp and stir continuously for 1-3 hours, then filter, wash and dry to obtain modified filler.

[0021] Preferably, in S1, the mass fraction of the ethanol solution is 70%-90%; the particle size of the allophane powder is 7.2-8.6 μm, and the specific surface area is 55-65 m 2 / g, the SiO2 content in the composition is greater than 32%, and the Al2O3 content is greater than 50%.

[0022] Preferably, in S1, the mass volume ratio of γ-aminopropyltriethoxysilane, allophane powder and ethanol solution is (0.12-0.36) g: (1-2) g: (20-30) mL.

[0023] Preferably, in S2, the mass volume ratio of allyl alcohol glycidyl ether, aminosilane-modified allophane and anhydrous ethanol is (0.47-0.94) g: (1-1.5) g: (40-60) mL.

[0024] Preferably, in S3, the mass volume ratio of allyl-modified allophane, 2-mercaptobenzimidazole and tetrahydrofuran is (1-1.5) g: (0.52-0.86) g: (40-60) mL.

[0025] Preferably, in S3, the initiator is dimethyl benzoate (DMPA), and the added amount is 4.5%-7.5% of 2-mercaptobenzimidazole.

[0026] In a second aspect, the present invention provides a method for preparing a composite thermal insulation material, comprising the following steps:

[0027] (1) Weighing nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, and ethylene-vinyl acetate copolymer, mixing them in an internal mixer, heating them to 120-130° C., and mixing them for 10-20 minutes to obtain a first mixed material;

[0028] (2) weighing a modified filler, a flame retardant, a lubricant and an antioxidant, adding them to the first mixture, and mixing them at 120-130° C. for 10-20 minutes to obtain a second mixture;

[0029] (3) Add the vulcanizing agent and the foaming agent to the second mixture, place it in a mold for vulcanization and foaming treatment, the treatment temperature is 135-165°C, the pressure is 6-10MPa, the treatment time is 0.5-1h, and after demolding and cooling, the desired product is obtained.

[0030] The beneficial effects of the present invention are:

[0031] 1. The composite thermal insulation material disclosed in the present invention is a rubber-plastic composite material, which is obtained by compounding nitrile rubber and styrene-butadiene rubber as rubber raw materials and polyvinyl chloride as plastic raw materials, and modified fillers, plasticizers, flame retardants and other additives are added thereto to improve the performance of the rubber-plastic material. The prepared composite thermal insulation material not only has excellent thermal insulation, but also has better strength, aging resistance and corrosion resistance than ordinary rubber-plastic materials.

[0032] 2. The improvement of the rubber and plastic materials in the present invention mainly lies in the improvement of the filler, and the filler used is modified allophane. Allophane is an aluminum silicate mineral material with a large specific surface area, good strength and high temperature resistance, and also good adsorption performance. The present invention has made a series of modifications to it, so that it can be used as a heat-insulating filler for rubber and plastic.

[0033] 3. The modification process of allophane according to the present invention comprises: firstly carrying out aminosilane modification to graft a large number of amino groups on its surface; then using the epoxy group in allyl alcohol glycidyl ether to combine with the amino group in the aminosilane-modified allophane to obtain allyl-modified allophane; finally, a mercapto-ene click reaction is carried out between the mercapto group in 2-mercaptobenzimidazole and the double bond in the allyl-modified allophane to finally prepare a modified filler.

[0034] 4. Compared with ordinary allophane, the modified allophane of the present invention has better compatibility with rubber and plastic materials. The prepared composite materials were tested and found that the performance improvement of the modified allophane on rubber and plastic materials is mainly reflected in strength, aging resistance and corrosion resistance. In addition, it can also ensure good flame retardancy and heat insulation, thereby ensuring excellent thermal insulation effect and safety performance during use. DETAILED DESCRIPTION

[0035] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0036] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0037] The particle size of the allophane powder used in the embodiment of the present invention is 7.2-8.6 μm, and the specific surface area is 55-65 m 2 / g, the SiO2 content in the composition is greater than 32%, and the Al2O3 content is greater than 50%.

[0038] The present invention will be further described below in conjunction with the following examples.

[0039] Example 1

[0040] A composite thermal insulation material, calculated by weight, comprising:

[0041] 65 parts of nitrile rubber, 30 parts of styrene-butadiene rubber, 24 parts of polyvinyl chloride, 8 parts of ethylene-vinyl acetate copolymer, 18 parts of modified filler, 10 parts of flame retardant, 2 parts of lubricant, 2.8 parts of vulcanizing agent, 2.2 parts of foaming agent and 0.9 parts of antioxidant.

[0042] The model of nitrile rubber is NBR2707; the model of styrene-butadiene rubber is SBR1500E; the parameters of ethylene-vinyl acetate copolymer (EVA) are: vinyl acetate (VA) content is 18wt%, melt index is 8g / 10min (190℃ / 2.16kg); the melt index of polyvinyl chloride is 15g / 10min (190℃ / 2.16kg), and the density is 1.37g / cm 3 The flame retardant is aluminum silicate; the lubricant is magnesium stearate; the vulcanizing agent is a mixture of sulfur and zinc dimethacrylate in a mass ratio of 4:1; the foaming agent is foaming agent AC; and the antioxidant is antioxidant 264.

[0043] The preparation method of the modified filler comprises:

[0044] S1. Mix γ-aminopropyltriethoxysilane and 70%-90% ethanol solution by mass, heat to 70-80°C and reflux for 2-4h, then add allophane powder, the mass volume ratio of γ-aminopropyltriethoxysilane, allophane powder and ethanol solution is 0.24g:1.5g:25mL, continue to reflux for 8h, filter to obtain filter residue, wash with pure water at least once, and vacuum dry to obtain aminosilane-modified allophane;

[0045] S2, dissolving allyl alcohol glycidyl ether in anhydrous ethanol, heating to 75°C and reflux for 0.5h, then adding aminosilane-modified allophane, the mass volume ratio of allyl alcohol glycidyl ether, aminosilane-modified allophane and anhydrous ethanol is 0.71g:1.2g:50mL, continuing to reflux and stir for 4h, filtering to obtain a filter residue, washing with ethanol at least once, and vacuum drying to obtain allyl-modified allophane;

[0046] S3. Add allyl-modified allophane and 2-mercaptobenzimidazole into tetrahydrofuran, the mass volume ratio of allyl-modified allophane, 2-mercaptobenzimidazole and tetrahydrofuran is 1.2g:0.69g:50mL, then add photoinitiator dimethyl benzoate (DMPA) in an amount of 6% of 2-mercaptobenzimidazole, place under ultraviolet lamp and stir continuously for 2h at a stirring speed of 200r / min, then filter to obtain filter residue, wash with ethanol at least once, and vacuum dry to obtain modified filler.

[0047] The preparation method of the composite thermal insulation material comprises the following steps:

[0048] (1) Weighing nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, and ethylene-vinyl acetate copolymer, mixing them in an internal mixer, heating them to 125° C., and mixing them for 15 minutes to obtain a first mixed material;

[0049] (2) weighing a modified filler, a flame retardant, a lubricant and an antioxidant, adding them to the first mixture, and mixing them at 125° C. for 15 minutes to obtain a second mixture;

[0050] (3) Add the vulcanizing agent and the foaming agent to the second mixture, place it in a mold for vulcanization and foaming treatment, the treatment temperature is 150° C., the pressure is 8 MPa, the treatment time is 0.6 h, and after demolding and cooling, the desired product is obtained.

[0051] Example 2

[0052] A composite thermal insulation material, calculated by weight, comprising:

[0053] 55 parts of nitrile rubber, 40 parts of styrene-butadiene rubber, 16 parts of polyvinyl chloride, 10 parts of ethylene-vinyl acetate copolymer, 13 parts of modified filler, 12 parts of flame retardant, 1 part of lubricant, 3.5 parts of vulcanizing agent, 1.5 parts of foaming agent and 1.2 parts of antioxidant.

[0054] The model of nitrile rubber is NBR2870; the model of styrene-butadiene rubber is SBR1502; the parameters of ethylene-vinyl acetate copolymer (EVA) are: vinyl acetate (VA) content is 18wt%, melt index is 8g / 10min (190℃ / 2.16kg); the melt index of polyvinyl chloride is 15g / 10min (190℃ / 2.16kg), and the density is 1.37g / cm 3 The flame retardant is calcium silicate; the lubricant is zinc stearate; the vulcanizing agent is a mixture of sulfur and zinc dimethacrylate in a mass ratio of 3:1; the foaming agent is foaming agent H; and the antioxidant is antioxidant 4010.

[0055] The preparation method of the modified filler comprises:

[0056] S1. Mix γ-aminopropyltriethoxysilane and 70% ethanol solution by mass, heat to 70°C and reflux for 2h, then add allophane powder, the mass volume ratio of γ-aminopropyltriethoxysilane, allophane powder and ethanol solution is 0.12g:1g:20mL, continue to reflux for 6h, filter to obtain filter residue, wash with pure water at least once, and vacuum dry to obtain aminosilane-modified allophane;

[0057] S2, dissolving allyl alcohol glycidyl ether in anhydrous ethanol, heating to 70°C and reflux for 0.3h, then adding aminosilane-modified allophane, the mass volume ratio of allyl alcohol glycidyl ether, aminosilane-modified allophane and anhydrous ethanol is 0.47g:1g:40mL, continuing to reflux and stir for 2h, filtering to obtain a filter residue, washing with ethanol at least once, and vacuum drying to obtain allyl-modified allophane;

[0058] S3. Add allyl-modified allophane and 2-mercaptobenzimidazole into tetrahydrofuran, the mass volume ratio of allyl-modified allophane, 2-mercaptobenzimidazole and tetrahydrofuran is 1g:0.52g:40mL, then add photoinitiator dimethyl benzoate (DMPA) in an amount of 4.5% of 2-mercaptobenzimidazole, place under ultraviolet lamp and stir continuously for 1h at a stirring speed of 100r / min, then filter to obtain filter residue, wash with ethanol at least once, and vacuum dry to obtain modified filler.

[0059] The preparation method of the composite thermal insulation material comprises the following steps:

[0060] (1) Weighing nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, and ethylene-vinyl acetate copolymer, mixing them in an internal mixer, heating them to 120° C., and mixing them for 10 minutes to obtain a first mixed material;

[0061] (2) weighing a modified filler, a flame retardant, a lubricant and an antioxidant, adding them to the first mixture, and mixing them at 120° C. for 10 minutes to obtain a second mixture;

[0062] (3) Add the vulcanizing agent and the foaming agent to the second mixture, place it in a mold for vulcanization and foaming treatment, the treatment temperature is 135° C., the pressure is 6 MPa, the treatment time is 0.5 h, and after demolding and cooling, the desired product is obtained.

[0063] Example 3

[0064] A composite thermal insulation material, calculated by weight, comprising:

[0065] 75 parts of nitrile rubber, 40 parts of styrene-butadiene rubber, 32 parts of polyvinyl chloride, 10 parts of ethylene-vinyl acetate copolymer, 26 parts of modified filler, 12 parts of flame retardant, 3 parts of lubricant, 3.5 parts of vulcanizing agent, 3 parts of foaming agent and 1.2 parts of antioxidant.

[0066] The model of nitrile rubber is NBR3345; the model of styrene-butadiene rubber is SBR1712; the parameters of ethylene-vinyl acetate copolymer (EVA) are: vinyl acetate (VA) content is 18wt%, melt index is 8g / 10min (190℃ / 2.16kg); the melt index of polyvinyl chloride is 15g / 10min (190℃ / 2.16kg), and the density is 1.37g / cm 3 The flame retardant is potassium aluminum silicate; the lubricant is sodium stearate; the vulcanizing agent is a mixture of sulfur and zinc dimethacrylate in a mass ratio of 6:1; the foaming agent is foaming agent OBSH; and the antioxidant is antioxidant 3100.

[0067] The preparation method of the modified filler comprises:

[0068] S1. Mix γ-aminopropyltriethoxysilane and 90% ethanol solution by mass, heat to 80°C and reflux for 4h, then add allophane powder, the mass volume ratio of γ-aminopropyltriethoxysilane, allophane powder and ethanol solution is 0.36g:2g:30mL, continue to reflux for 10h, filter to obtain filter residue, wash with pure water at least once, and vacuum dry to obtain aminosilane-modified allophane;

[0069] S2, dissolving allyl alcohol glycidyl ether in anhydrous ethanol, heating to 80°C and reflux for 0.8h, then adding aminosilane-modified allophane, the mass volume ratio of allyl alcohol glycidyl ether, aminosilane-modified allophane and anhydrous ethanol is 0.94g:1.5g:60mL, continuing to reflux and stir for 6h, filtering to obtain a filter residue, washing with ethanol at least once, and vacuum drying to obtain allyl-modified allophane;

[0070] S3. Add allyl-modified allophane and 2-mercaptobenzimidazole into tetrahydrofuran, the mass volume ratio of allyl-modified allophane, 2-mercaptobenzimidazole and tetrahydrofuran is 1.5g:0.86g:60mL, then add photoinitiator dimethyl benzoate (DMPA) in an amount of 7.5% of 2-mercaptobenzimidazole, place under ultraviolet lamp and stir continuously for 3h at a stirring speed of 300r / min, then filter to obtain filter residue, wash with ethanol at least once, and vacuum dry to obtain modified filler.

[0071] The preparation method of the composite thermal insulation material comprises the following steps:

[0072] (1) Weighing nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, and ethylene-vinyl acetate copolymer, mixing them in an internal mixer, heating them to 130° C., and mixing them for 20 minutes to obtain a first mixed material;

[0073] (2) weighing a modified filler, a flame retardant, a lubricant and an antioxidant, adding them to the first mixture, and mixing at 130° C. for 20 minutes to obtain a second mixture;

[0074] (3) Add the vulcanizing agent and the foaming agent to the second mixture, place it in a mold for vulcanization and foaming treatment, the treatment temperature is 165°C, the pressure is 10MPa, the treatment time is 1h, and after demolding and cooling, the desired product is obtained.

[0075] Comparative Example 1

[0076] A composite thermal insulation material, which is different from Example 1 only in that the modified filler is replaced by allophane.

[0077] Comparative Example 2

[0078] A composite thermal insulation material, which differs from Example 1 only in that the modified filler is replaced by allyl-modified allophane (prepared in the same way as Example 1).

[0079] Comparative Example 3

[0080] A composite thermal insulation material, which is different from Example 1 only in that the modified filler is replaced by a mixture of allophane and 2-mercaptobenzimidazole, and the mass ratio of allophane to 2-mercaptobenzimidazole is 1.2:0.69.

[0081] Experimental testing

[0082] The properties of the composite thermal insulation materials prepared in Example 1 and Comparative Examples 1-3 were tested. The tensile strength was based on GB / T 528-2009, the thermal conductivity was based on GB / T 11205-2009, the oxygen index was based on ASTM D2863, and the aging resistance test was as follows: 2The steel sheet was irradiated under a xenon lamp for 300 hours to observe whether its surface was cracked. The corrosion resistance test was: soaked in a 10wt% sodium chloride salt solution at 60°C for 168 hours, then its tensile strength was tested and the change rate was calculated.

[0083] The data detection results are shown in Table 1:

[0084] Table 1 Performance results of different materials

[0085]

[0086] It can be seen from the test results in Table 1 that the strength, aging resistance and salt corrosion resistance of the composite thermal insulation material prepared in Example 1 are significantly improved. In addition, the thermal conductivity and flame retardancy are also slightly improved, indicating that it can have good thermal insulation effect and safety performance when used.

[0087] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0088] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A composite thermal insulation material, characterized in that: Calculated by weight, including: 55-75 parts of nitrile rubber, 20-40 parts of styrene-butadiene rubber, 16-32 parts of polyvinyl chloride, 5-10 parts of ethylene-vinyl acetate copolymer, 13-26 parts of modified filler, 6-12 parts of flame retardant, 1-3 parts of lubricant, 2.1-3.5 parts of vulcanizing agent, 1.5-3 parts of foaming agent and 0.6-1.2 parts of antioxidant; The modified filler is prepared by sequentially subjecting allophane to aminosilane modification and allyl modification, and then compounding with 2-mercaptobenzimidazole.

2. A composite thermal insulation material according to claim 1, characterized in that: The model of the nitrile rubber is one of NBR2707, NBR2870 and NBR3345; the model of the styrene butadiene rubber is one of SBR1500E, SBR1502 and SBR1712.

3. The composite thermal insulation material according to claim 1, characterized in that: The parameters of the ethylene-vinyl acetate copolymer (EVA) are: the content of vinyl acetate (VA) is 18wt%, the melt index is 8g / 10min (190°C / 2.16kg); the melt index of the polyvinyl chloride is 13-18g / 10min (190°C / 2.16kg), and the density is 1.36-1.39g / cm 3 .

4. The composite thermal insulation material according to claim 1, characterized in that: The flame retardant is an inorganic silicon flame retardant, including any one of aluminum silicate, calcium silicate, and potassium aluminum silicate; the lubricant is any one of magnesium stearate, zinc stearate, and sodium stearate; and the vulcanizing agent is a mixture of sulfur and zinc dimethacrylate in a mass ratio of 3-6:

1.

5. The composite thermal insulation material according to claim 1, characterized in that: The foaming agent is any one of foaming agent AC, foaming agent H, and foaming agent OBSH; the antioxidant is any one of antioxidant 264, antioxidant 4010, antioxidant 3100, and antioxidant 4020.

6. The composite thermal insulation material according to claim 1, characterized in that: The preparation method of the modified filler comprises: S1, γ-aminopropyltriethoxysilane and ethanol solution are mixed, heated and refluxed for 2-4 hours, then allophane powder is added, refluxed for 6-10 hours, filtered, washed and dried to obtain aminosilane-modified allophane; S2, dissolving allyl alcohol glycidyl ether in anhydrous ethanol, heating and refluxing for 0.3-0.8h, then adding aminosilane-modified allophane, continuing to reflux and stir for 2-6h, filtering, washing and drying to obtain allyl-modified allophane; S3. Add allyl-modified allophane, 2-mercaptobenzimidazole and initiator into tetrahydrofuran, place under ultraviolet lamp and stir continuously for 1-3 hours, then filter, wash and dry to obtain modified filler.

7. The composite thermal insulation material according to claim 6, characterized in that: In the S1, the mass volume ratio of γ-aminopropyltriethoxysilane, allophane powder and ethanol solution is (0.12-0.36) g: (1-2) g: (20-30) mL.

8. The composite thermal insulation material according to claim 6, characterized in that: In S2, the mass volume ratio of allyl alcohol glycidyl ether, aminosilane-modified allophane and anhydrous ethanol is (0.47-0.94) g: (1-1.5) g: (40-60) mL.

9. The composite thermal insulation material according to claim 6, characterized in that: In S3, the mass volume ratio of allyl-modified allophane, 2-mercaptobenzimidazole and tetrahydrofuran is (1-1.5) g: (0.52-0.86) g: (40-60) mL; the initiator is dimethyl benzoate (DMPA), and the added amount is 4.5%-7.5% of 2-mercaptobenzimidazole.

10. A method for preparing the composite thermal insulation material according to claim 1, characterized in that: The following steps are involved: (1) Weighing nitrile rubber, styrene-butadiene rubber, polyvinyl chloride, and ethylene-vinyl acetate copolymer, mixing them in an internal mixer, heating them to 120-130° C., and mixing them for 10-20 minutes to obtain a first mixed material; (2) weighing a modified filler, a flame retardant, a lubricant and an antioxidant, adding them to the first mixture, and mixing them at 120-130° C. for 10-20 minutes to obtain a second mixture; (3) Add the vulcanizing agent and the foaming agent to the second mixture, place it in a mold for vulcanization and foaming treatment, the treatment temperature is 135-165°C, the pressure is 6-10MPa, the treatment time is 0.5-1h, and after demolding and cooling, the desired product is obtained.

Citation Information

Patent Citations

  • Graphene oxide modified anti-ageing agent, anti-thermo-oxidative-aging rubber containing graphene oxide modified anti-ageing agent and preparation method

    CN110117390A

  • Flame-retardant antistatic rubber V belt and preparation method thereof

    CN116987331A

  • Polycarbonate alloy and preparation method thereof

    CN118421066A

  • Filler subjected to surface treatment and resin composition prepared using the same

    JP2015214655A